International case studies on tourism destination management and COVID-19 impacts and responses - Hudson, Simon (London New York, NY Routledge, Taylor & Francis Group, 2023)
"International Cases on Tourism Destination Management and COVID-19 provides students, lecturers and practitioners with an essential real-life resource on how different tourism destinations around the world have been impacted by, and responded to, the COVID-19 pandemic. This is an essential resource for tourism students and lecturers across the curriculum, and a fascinating read for anyone in the business of tourism"--
Includes bibliographical references and index.
Keywords: COVID-19 Pandemic, 2020-2023 -- Case studies; Tourism -- Health aspects -- Case studies; Tourism -- Management -- Case studies; Case studies